Transformasi Perkembangan Kurikulum ’Dini Islami Rabi’ Thanawi’ di Negeri Selangor Dari Tahun 1960-an Sehingga 1970-an: Transformation of Curricular Developments For Islami Rabi’ Thanawi in the State of Selangor (1960-1970) - Mat Jusoh, Zaihan Hairuzialani; Abdul Hamid, Ahmad Faisal; Hussin, Zaharah (Journal Al-Muqaddimah, 2019)
Islamic education in the state of Selangor has been formally evolved since the 1960s, the development has undergone a transformation from several aspects such as the level of education and infrastructure, flow, content orientation, approach and administration. To discuss the matter an objective has been outlined. (1) To produce new themes in aspects that have influenced the historical transformation of the development of Islamic Education in Selangor from the 1960s until the 1970s. Secondary sources as well as primary sources will be referred to as sources of information for the writing of this article, including updates on historical information of the Selangor religious schools in the 1960s, teachers’ files from the 1940s, minutes of meetings and interviews. The conclusion can be summarized that the influence of the involvement of religious teachers as the power and influence of the Sultan is an important discovery that has been the core of the transformation of the Rabi ’Thanawi Islamic Curriculum in the state of Selangor from the 1960s to the 1970s.